Penggunaan Model Utaut dan ISSM untuk Menganalisis Niat Mahasiswa Menggunakan Kembali Website DDTC Sebagai Sumber Literasi Perpajakan (Studi Kasus pada Mahasiswa D3 dan S1 Perpajakan Universitas Brawijaya) - Andrean Nathaniel; Alfina Auliyaul Chusna; Irfan Isa Mahendra; Kharissima Ndaru Amallia; Kadek Dwi Premana; Yuni Maria Parsaulian Simbolon; Agung Nugroho Luthfi Imam Fahrudi (JEMAP, 2024)
This study aims to identify the factors influencing students' intention to use the tax literacy website, DDTC, by employing the UTAUT and ISSM models. The research was conducted at the University of Brawijaya, focusing on active students from the D3 Vocational and Bachelor's Degree Programs in Taxation. The research methodology employed was quantitative and explanatory in nature. Non-probability sampling was used to select a sample of 161 students. Data collection was carried out through questionnaires and analyzed using the Partial Least Squares Structural Equation Modeling (PLS-SEM) technique. The results of this study indicate that all of the X variables exhibit a positive influence on the Y variable. However, among the seven X variables, only one of them yielded a significant result, which is Facilitating Conditions, showing a positive but non-significant impact on Reuse Intention. Meanwhile, Performance Expectancy, Effort Expectancy, Social Influence, Information Quality, Service Quality, and System Quality all demonstrated a positive yet non-significant influence on the Reuse Intention variable.